Child protection in sport and recreation guidelines for achieving child protection for sport and recreation clubs. - New South Wales. Department of Sport and Recreation (Sydney, N.S.W. : NSW Department of Sport and Recreation, 2003)
"This booklet provides key information that sport and recreation clubs and groups will need to know to achieve child protection. An interactive web site www.dsr.nsw.gov.au will also be available, with practical examples of situations that will be valuable to clubs and groups" -- Introduction.
"June 2003".
Title from title screen (viewed February 17, 2004).
Mode of access: World Wide Web. Available at: http://www.dsr.nsw.gov.au/assets/pubs/wwcc/cp_clubguide.pdf
System requirements: Adobe Acrobat Reader required to view/print PDF files.
Selected for archiving
Keywords: Child abuse -- New South Wales -- Prevention; Children -- Crimes against -- New South Wales -- Prevention; Sports for children -- New South Wales